Looking for love in the legal discourse of marriage - Grossi, Renata (ANU E Press, 2014)
This book examines the (in)visibility of romantic love in the legal discourse surrounding modern Australian marriage. It looks at how romantic love has become a core part of modernity, and a dominant part of the Western marriage discourse, and considers how the ideologies of romantic love are (or are not) replicated in the legal meaning of marriage. This examination raises two key issues. If love has become central to people's understanding of marriage, then it is important for the legitimacy of law that love is reflected in both the content and application of the law. More fundamentally, it requires us to reconsider how we understand law, and to ask whether it is engaged with emotions, or separate from them. Along the way this book also considers the meaning of love itself in contemporary society, and asks whether love is a radical force capable of breaking down conservative meanings embedded in institutions like marriage, or whether it simply mirrors them. This book will be of interest to everyone working on love, marriage and sexuality in the disciplines of law, sociology and philosophy.